Lichens: a novel and potential source as antimicrobials for human use - Devaraja, Gayathri; T, Swamy C (Journal of Phytology, 2012)
The use of lichens in medicine is based on the fact that they contain unique and varied biologically active substances, as antimicrobials.Â Since they are natural antibiotics, their metabolites exert a wide variety of biological actions including antimycotic, antiviral, anti-inflammatory, analgesic, antipyretic, antiproliferative, and cytotoxic effects, they are considered as potential drugs. They contain a variety of secondary metabolites with strong antioxidant activity. These are substances which have high ability to scavenge toxic free radicals due their phenolic groups. These manifold activities of lichen metabolites have now been recognized, and therefore their therapeutic potential have great impact in pharma industries. The present article discusses the importance of lichens in inhibiting various types of human pathogens in addition to their chemical composition and pharmacological activities.